Fibroblast Growth Factor‐23 and Frailty in Elderly Community‐Dwelling Individuals: The Cardiovascular Health Study. Issue 2 (February 2016) - Beben, Tomasz; Ix, Joachim H.; Shlipak, Michael G.; Sarnak, Mark J.; Fried, Linda F.; Hoofnagle, Andrew N.; Chonchol, Michel; Kestenbaum, Bryan R.; de Boer, Ian H.; Rifkin, Dena E.
Abstract : Objectives: To evaluate whether fibroblast growth factor 23 (FGF‐23) is related to frailty and to characterize the nature of their joint association with mortality. Design: Cross‐sectional analysis for frailty and longitudinal cohort analysis for mortality. Setting: Cardiovascular Health Study. Participants: Community‐dwelling individuals (N = 2, 977; mean age 77.9 ± 4.7, 40% male, 83% white). Measurements: The predictor was serum FGF‐23 concentration (C‐terminal enzyme‐linked immunosorbent assay), and the outcomes were frailty status (determined according to frailty phenotype criteria of weight loss, weakness, exhaustion, slowness, and low physical activity) and mortality. Multinomial logistic regression was used to assess the cross‐sectional association between FGF‐23 and frailty and prefrailty, adjusting for demographic characteristics, cardiovascular disease and risk factors, and kidney markers. Proportional hazards Cox proportional hazards regression was used to assess the association between FGF‐23, frailty, and all‐cause mortality. Results: Mean estimated glomerular filtration rate (eGFR) was 64 ± 17 mL/min per 1.73 m 2 . Median FGF‐23 was 70.3 RU/mL (interquartile range 53.4–99.2); 52% were prefrail, and 13% were frail. After multivariate adjustment, each doubling in FGF‐23 concentration was associated with 38% (95% confidence interval (CI) = 17–62%) higher odds of frailty than of nonfrailty and 16% (95% CI = 3–30%) higher odds of prefrailty. FGF‐23 (hazard ratio (HR) = 1.16, 95% CI = 1.10–1.23) and frailty (HR = 1.82, 95% CI = 1.57–2.12) were independently associated with mortality, but neither association was meaningfully attenuated when adjusted for the other. Conclusion: In a large cohort of older adults, higher FGF‐23 was independently associated with prevalent frailty and prefrailty. FGF‐23 and frailty were independent and additive risk factors for mortality. FGF‐23 may be a marker for functional outcomes.